International Technical Cooperation Agreements in Colombia, Vaccination Vulnerable Population (2014)
The results demonstrate the steps taken by the international technical cooperation in the health sector in Colombia, plays a great role in the development and implementation of public policies to eradicate and improve existing social and public health problem in the country